2022
DOI: 10.3390/ijerph19138208
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life and Perceived Burden of Informal Caregivers of Patients with Rare Diseases in Selected European Countries

Abstract: Most of rare disease (RD) patients are assisted in their homes by their family as informal caregivers, causing a substantial burden among family members devoted to care. The role of informal caregivers has been associated with increased levels of stress, poor physical/mental health and impaired HRQOL. The present study assessed the impact on HRQOL and perceived burden of long-term informal caregiving, as well as the inter-relationships of individuals affected by different RD in six European countries, taking a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…This hypothesis was robust even after accounting for key socio-economic, cultural, demographic and healthcare factors. In general, the findings corroborate existing evidence in Europe [ 32 ], and Asia [ 33 ]. For example, Hsiao and colleagues [ 33 ] report that primary caregivers of older adults who experienced higher levels of caregiver burden also reported poor health-related quality of life.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…This hypothesis was robust even after accounting for key socio-economic, cultural, demographic and healthcare factors. In general, the findings corroborate existing evidence in Europe [ 32 ], and Asia [ 33 ]. For example, Hsiao and colleagues [ 33 ] report that primary caregivers of older adults who experienced higher levels of caregiver burden also reported poor health-related quality of life.…”
Section: Resultssupporting
confidence: 89%
“…In a published study across six European countries (France, Germany, Italy, Spain, Sweden, and UK), Valcárcel-Nazco et al [ 32 ] found a negative correlation between informal caregivers’ health-related quality of life and caregiver burden. Also, in a cross-sectional study on caregiver burden and health-related quality of life among primary family caregivers of individuals with schizophrenia in Taiwan, Hsiao et al [ 33 ] found that primary family caregivers who experienced mild to moderate caregiver burden had poor health-related quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…54% of patients surveyed in the USA also reported that their rare disease had led to isolation from friends [ 23 ]. Not only the patients themselves, but also relatives and caregivers are heavily burdened by the patients’ health situation [ 23 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…A symbiosis between ERN and medical universities could generate great added value for all European RD stakeholders. Another major international tool for dissemination and promotion of knowledge about RD is the Orphanet portal for RD and orphan drugs [40][41][42][43]. Over the past 25 years of activity, Orphanet has become the leading reference source of information on RD and has helped shape the RD landscape in Europe and around the world.…”
Section: Discussionmentioning
confidence: 99%